Correction: Asonitou, K.; Koutsouki, D. PASS Theory and Movement Disorders: Methodology for Assessment and Intervention. Children 2024, 11, 1192 - Katerina Asonitou; Dimitra Koutsouki (MDPI AG, 2024)
In the original publication [...]